REORIENTATION OF INDIVIDUAL-TRANSCENDENTAL SUFISM VALUES IN AT-TUHFAH AL-MURSALAH MANUSCRIPT TOWARD SOCIO-EMPIRICAL VALUE - Ihsan Sa'dudin (Universitas Islam Negeri Alauddin Makassar, 2018)
The manuscript at-Tuhfah al-Mursalah a track record of the past is full of virtues. Seeking virtue means preparing yourself through the purification process. Sufism, as a purification step to reach the Allah. The spiritual experience gained by salik when meeting and union with Allah (individual-transcendental values) should be felt also by others. The transmission of spiritual experience is implemented in empirical life (socio-empirical values) as a form of practicing and teaching a loving Islam, so that the concept of rahmatan lil 'alamin can be felt by all creatures. The process of attaining the maqam requires clarity of heart; peace of mind, mind and environment; as well as sincerity amaliyah. Awareness to negate the existence of self (‘alam nasut) and purify the existence of divinity (‘alam lahut) in self as a form of preparation to accept the holiness of the Khaliq. It is this doctrine of purity that should be practiced and spread by the salik and perceived by all beings to create goodness in the universe. Goodness that does not look to ethnic, religious, ethnic, and state boundaries. Universal goodness as the real essence of Islam rahmatan lil a'lamin.